Topical corticosteroid use during pregnancy - Alabdulrazzaq, Fatoumah (College of Family Physicians of Canada, 2012)
Question Some of my pregnant patients have been prescribed various potencies of topical corticosteroids. Do these carry the same fetal risks as systemic corticosteroids? Answer Pregnant women can be reassured that there is no apparent increased risk of adverse fetal effects when using topical corticosteroids during pregnancy, although some data do suggest fetal growth restriction with more potent topical corticosteroids. Overall, women should be prescribed the lowest potency required whenever possible.